Hubungan Sifat Fisika dan Kimia Tanah dengan Persentase Penyakit Layu pada Tanaman Cengkeh (Syzygium aromaticum l.) yang Disebabkan oleh Jamur Akar Putih (rigidoporus sp.) di Desa Unggahan, Kabupaten Buleleng - APRIAST, PUTU AGUSIKA; SUDANA, I MADE; SUDARMA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.4, No.1, Januari 2015, 2015)
Correlation Soil Physical and Chemical Properties with Disease Incidence on Plants Clove (Syzygium aromaticum L.) Caused by White Root Fungus ( Rigidoporus sp.) in Unggahan Village, Buleleng Regency Correlation soil physical and chemical properties with disease incidence on plants clove (Syzygium aromaticum L.) caused by white root fungus ( Rigidoporus sp.) In the village of Unggahan, Buleleng Regency aims to determine the correlation between physical and chemical properties of the soil with the disease incidence the clove plant wilt disease and the rate of infection in plants cloves.The method used in this study is a survey method.This research was conducted at three locations of the different by taking five samples randomly cloves at each study site.The results showed that soil physical and chemical properties that have a real relationship with the percentage of wilt disease in plants clove is soil organic matter, soil pH, soil temperature, and soil moisture.Soil organic matter, soil pH, and soil temperature has a negative correlation with the percentage of wilt disease on the clove plant, while soil moisture has a positive correlation with the disease incidence in plants cloves.The infection rate in the three study sites showed the same average is 0.1 per unit per day. Keywords: physical and chemical properties of the soil, the percentage of disease, and the infection rate
Keywords: physical and chemical properties of soil; percentage of disease; infection rate